Use of Microfocused X-ray Techniques to Investigate the Mobilization of As by Oxalic Acid - Wovkulich, Karen (2012)
Improved linkages between aqueous phase transport and solid-phase reactions are needed to better predict and model transport of contaminants through the subsurface. Here we develop and apply a new method for measuring As mobilization in situ within soil columns that utilizes synchrotron-based X-ray fluorescence. By performing these measurements in situ during column transport experiments, we simultaneously monitor grain-scale solid phase reactions and column-scale transport. Arsenic may be effectively mobilized by oxalic acid but the geochemical and mineralogical factors that influence the rate and extent of mobilization are not well understood. Column experiments (~4 cm long × 0.635 cm ID) using As contaminated sediments from the Vineland Chemical Company Superfund site were performed on the laboratory bench as well as in the synchrotron beamline. Microfocused synchrotron X-ray fluorescence (μSXRF) maps for As and Fe were collected at the same location in the columns (<1 mm(2)) before and during treatment with 10 mM oxalic acid. The fraction of As and Fe removed by oxalic acid treatment was calculated from the change in flux-normalized counts for each pixel in the map images, and these data were used to calculate kinetic parameters over the studied area. Between 79% and 83% of the As was removed from the sediments by the oxalic acid treatment based on μSXRF data; these removal percentages agreed well with laboratory data based on column effluent (88–95%). Considerably less Fe was removed by oxalic acid treatment, 14–25% based on μSXRF counts, which is somewhat higher than the 7–9% calculated from laboratory column effluent concentrations. Microfocused X-ray absorption near edge spectroscopy (μXANES) on a subset of points indicates most of the Fe was oxidized and present as a mixture of goethite, hematite, and ferrihydrite on sand grain coatings. Treatment with oxalic acid led to subtle shifts in Fe (III) species following oxalic acid treatment, either removing ferrihydrite or transforming it to more stable oxides; however, Fe redox states were not impacted. Kinetics information extracted from μSXRF data compared favorably with rates of As removal from observed As breakthrough curves. The average pseudo-first order As removal rate constant was calculated to be 0.015 min(−1) ± 0.002 (± average standard error, N=400) based on changes in μSXRF counts over time. The spatial variation observed in the rate constant is likely a result of differences in the mineral substrate or As retention mechanism. Geochemical models created using the calculated As removal rate constants showed agreement with As breakthrough curves for both a small column (4.25 cm × 0.635 cm ID) and a larger column (23.5 cm × 4.2 cm ID), indicating that the processes studied using the microprobe are representative and often can be predictive of larger systems. While this work was used to understand the processes that regulate As release and transport, the methods developed here could be used to study a wide variety of reaction processes, including contaminant removal due to chemical treatment, mineral precipitation due to changing redox characteristics, and solid phase transformations.